Marketing Management Of Msme Products, Serang City Groups of Era New Normal - Erika Febriani; Chelsea Tiara Septiani Malau; Puput Adela; Rio Primus; Raissa Tsabitha; Alvandri Christian Rahmat Gulo; Ridho Pangestu Taufik; Mohamad Fasyehhudin; Belardo Prasetya Mega Jaya; Jefry Winter Luhut Hasudungan (MOVE: Journal of Community Service and Engagement, 2022)
During this new normal era, each sector gets its own impact, such as starting to recover and the resumption of movement, one of which is the economic sector. Where business actors who take an important role in the wheels of the national economy must be a concern and focus for the government. Based on this, the institution through academics then mobilized students in the Matching Fund program to do community service, especially MSMEs in Serang City, therefore a group called Nine Outlets was formed to then focus on honing the entrepreneurial spirit related to the Marketing Management of MSME Products in Serang City in Groups in the New Era. It is normal to agree on several MSMEs, namely Food and Beverage/Imara Balok Cake, Damory Chocolate Banana, and Sale Pisang and Ori 72 Banana Chips to market these products in groups by utilizing technology through social media as a tool for product marketing, with the aim of reaching a wider market large.